THE INFLUENCE OF WATTPAD APPLICATION TOWARDS STUDENTS’ WRITING SKILLS ACHEVEMENT OF 10TH GRADE AT SMAN 1 SUKOMORO - Meira Rachmawati; Nurhamid (Journal of English Language Education, 2025)
Observations of 10th grade students at SMAN 1 Sukomoro reveal significant challenges in their writing skills, though students using the Wattpad application tend to overcome these difficulties. This research aims to (1) assess the writing skills achievement of 10th grade students at SMAN 1 Sukomoro who do not use Wattpad Application, (2) evaluate the writing skills achievement of those who use Wattpad Application, and (3) determine the significant influence of Wattpad Application on students' writing skills. A quantitative approach with a causal comparative design was used, employing Independent Sample t-Test for data analysis. Data was collected through tests and documentation from two classes: one using Wattpad and one not, with a sample of 70 students from classes 10-3 and 10-4 out of a total population of 317 students. Purposive sampling was applied. The Independent t-Test showed a tcount >ttable (9,784 > 3,980) and Sig. (2-tailed) of 0.000 > 0.05. This indicates a significant influence of Wattpad on students' writing skills achievement The findings confirms that the Wattpad application significantly influence on students' writing skills.